’Wordt Nederland verdedigd?’ De discussie over de hoofdverdedigingslinie van de NAVO in het begin van de jaren vijftig - Hoffenaar, J. (BMGN - Low Countries Historical Review, 2004)
‘Will the Netherlands be defended?’ The debate about NATO’s main lines of defence at the beginning of the 1950s At the beginning of the 1950s, the Netherlands would not have been able to defend itself in the event of a Soviet attack. Despite the fact that NATO, under the leadership of the Supreme Allied Commander Europe, General Eisenhower, and later General Ridgway, was in the process of rapidly building up its defences, it was still incapable of conducting a forward defence. The pivotal political and military issue in the short term centred on one question: Which areas in Western Europe could and should be kept and which not? Answers to this question exposed conflicting national interests and points of view, particularly those of the Dutch and the French. As it was taking a considerably long time to build up the Netherlands’ defences, the Dutch government had very few trump cards to add weight to its demands. Indeed, in the summer of 1952, when Parliament asked to be given a precise account of how the Dutch defences were progressing, the government was practically boxed into a corner.